Development of 43 maize hybrids with high yield potential and competitive agronomic characteristics for the mid-altitudes of Mexico and lowland tropical of Latin-America - CGIAR Research Program on Maize (2021)
Stage 3 maize hybrids were tested in seven different trials across 5-10 sites in Mexico and 43 hybrids were selected as candidates for advancement to Stage 4 hybrids evaluation during 2022.